(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Serosero RH, Sulistiono, Butet NA, Riani E. 2021. Stock status of coconut crab (Birgus latro) in Daeo, Morotai Island District, North Maluku, Indonesia. Biodiversitas 22: 626-634. The populations of coconut crabs (Birgus latro) in nature continue to decline due to their simple capture for human consumption. This study aimed to determine the status of coconut crab stock in Daeo, Morotai Island Regency, North Maluku, Indonesia including estimations of growth parameters and population size. This research was conducted from October 2016 to September 2017. Growth parameters were estimated based on 12 monthly length-frequency samples. Data analysis was carried out using the ELEFAN I method on the FiSAT II program for estimating growth parameters, and the Schnabel method for estimating population size. The results showed that the level of exploitation of male and female coconut crabs in Daeo was high (E > 0.5). The asymptotic length L? for males was 56.96 mm thoracic length (TL) and that of females 52.50 mm TL. The growth coefficient K for males was 0.14 and that for females 0.16. Length to is -1.026 (male) and -0.913 (female). The results generated using the Schnabel method suggested that the population size of the coconut crab in Daeo was 7,466 to 73,948 individuals considering a confidence interval of 95%. The recapture of tagged coconut crabs was merely 0. 82%.